The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3354/meps334273
|View full text |Cite
|
Sign up to set email alerts
|

Winter energy storage dynamics and cohort structure of young-of-the-year bluefish Pomatomus saltatrix off North Carolina

Abstract: The ecology of overwintering young-of-the-year bluefish Pomatomus saltatrix off North Carolina, USA, was examined for the 2001 and 2002 year-classes, to test the hypothesis that overwinter mortality affects the recruitment of summer-spawned bluefish. A trawling survey was conducted in Onslow Bay, North Carolina, from October 2001 to May 2002 and from September 2002 to June 2003 to determine bluefish abundance, cohort structure, energy density of white muscle and liver, and gut fullness. Up to 4 transects rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 42 publications
3
35
2
Order By: Relevance
“…On 19 November 2001, tanks were stocked with 15 SP or SU bluefish (n = 3 replicate tanks per treatment combination). Cohort assignment was based on bimodal length/frequency distributions of YOY bluefish collected in NC during fall 2001 (Morley et al 2007). Mean (± SD) initial fork lengths (FL) of SP and SU bluefish were 264 ± 16.6 mm and 206 ± 12.0 mm, respectively (Student's t-test, p < 0.01).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…On 19 November 2001, tanks were stocked with 15 SP or SU bluefish (n = 3 replicate tanks per treatment combination). Cohort assignment was based on bimodal length/frequency distributions of YOY bluefish collected in NC during fall 2001 (Morley et al 2007). Mean (± SD) initial fork lengths (FL) of SP and SU bluefish were 264 ± 16.6 mm and 206 ± 12.0 mm, respectively (Student's t-test, p < 0.01).…”
Section: Methodsmentioning
confidence: 99%
“…Wild bluefish for this analysis were trawled from continental shelf (5 to 20 m depth) habitats in Onslow Bay, North Carolina, during February and May 2002 (Morley et al 2007). Condition indices included liver dry mass, liver lipid and ash content, WM lipid density, WM ash content and total wet body mass.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, due to the lack of previously published studies that report summer lipid values for age-0 bluefish, we were unable to compare the cohort-specific C:N lipid proxy patterns that we observed to values from the same month(s) from other regions or years. Still, it is worth noting recent work by Slater et al (2007) and Morley et al (2007) that found that spring and summer cohorts of age-0 bluefish manifested different energy allocation strategies by fall; members of the spring-spawned cohort entered the October-November overwintering period with higher lipid reserves than summerspawned fish that presumably shunted more energy into somatic growth. We observed the opposite pattern, i.e.…”
Section: Conditionmentioning
confidence: 99%